The Effect of Return on Asset, Return on Equity, Debt to Equity Ratio, Earning Per Share, and Price Earning Ratio on Company Value - Muharrom, Ibnu; Norisanti, Nor; Komariah, Kokom (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the magnitude of the influence of Return On Asset, Return On Equity, Debt To Equity Ratio, Earning Per Share and Price Earning Ratio on the Value of the Indonesia Stock Exchange Company in 2019-2023 in the company PT. Bukit Uluwatu Villa Tbk., PT. Destinasi Tirta Nusantara Tbk., PT. Pembangunan Graha Lestari Indah Tbk. PT. Pembangunan Jaya Ancol Tbk., PT. Eastparch Hotel Tbk. And PT. Pioneerindo Gourmet Internasional Tbk partially and simultaneously. The method used in this study is a descriptive verification method. The data used are secondary data obtained from BEI data and/or annual report data for each company which includes data on Return On Asset, Return On Equity, Debt To Equity Ratio, Earning Per Share and Price Earning Ratio and Company Value. Statistical tests used in this study are classical assumption tests, correlation coefficient analysis, determination coefficient analysis and hypothesis testing using the SPSS Statistics software program. The 36.5% influence of ROA, ROE, DER, EPS, and PER on company value indicates a significant but not dominant influence. This means that while these factors are important, companies must also consider external factors and non-financial business strategies to increase their company value. Furthermore, investors should consider other factors before making investment decisions.